Does hiatal hernia impact gastro-oesophageal reflux-related chronic cough? - Olga Truba; Joanna Żuchowska; Elżbieta M. Grabczak; Katarzyna Białek-Gosk; Aleksandra Rybka-Frączek; Rafał Krenke; Marta Dąbrowska (ERJ Open Research, 2023)
Background Hiatal hernia may coexist with gastro-oesophageal reflux (GOR)-related chronic cough. This study aimed to evaluate whether the presence of hiatal hernia was related to chronic cough severity and the response to antireflux therapy. Methods This was a retrospective analysis of data on adults with GOR-related chronic cough managed in our cough centre between 2017 and 2021. Patients who had undergone chest computed tomography (CT) and in whom follow-up data were available were included. The presence and size of hiatal hernia were assessed based on thorax CT scanning. Patients were treated with modification of diet and proton pump inhibitors. The response to treatment was assessed by the change in quality of life (QOL) measured by Leicester Cough Questionnaire (LCQ) and cough severity was measured by 100-mm visual analogue scale. Results 45 adults (28 female, 17 male) were included. Hiatal hernia was demonstrated in 12 (26.6%) patients. Patients with hiatal hernia did not differ from those without hiatal hernia in clinical characteristics, cough duration and severity and cough-related QOL. We found moderate positive correlations between maximal sagittal diameter of hiatal hernia and cough severity (ρ=0.692, p=0.013) and duration (ρ=0.720, p=0.008). Patients without hiatal hernia responded better to antireflux therapy, with significant LCQ improvement. A strong negative correlation between sagittal diameter of hiatal hernia gate and increase in LCQ (ρ= −0.764, p=0.004) was demonstrated. Conclusion The presence of hiatal hernia identified in chest CT may impact cough severity, duration and response to antireflux treatment in patients with GOR-related chronic cough. Further prospective studies are justified to confirm significance of hiatal hernia in the management of chronic cough.